Service Reliability, Service Value, and Timeliness as Drivers of Customer Loyalty: The Mediating Roles of Relationship Marketing and Customer Satisfaction in Corporate Logistics Services - Della Galuh Anastasia; Maniah Maniah; Erna Mulyati (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
One of decisive challenges faced within business-to-business (B2B) logistics industry is maintaining customer loyalty due to customer expectations and inconsistent findings increasement regarding its determinants. The impacts analysis towards service reliability and value, also timeliness onto customer loyalty were developed extensively in this research, using relationship marketing as well customer satisfaction for corporate logistics services at PT Pos Indonesia (Persero). A quantitative descriptive-verificative methodology was applied. Purposive sampling technique was used to collect 157 corporate customers data eligibly in Regional 2 Jakarta to get examined with Partial Least Squares Structural Equation Modeling (PLS-SEM). Test outcome explains service reliability (β = 0.279; t = 2.298) and timeliness (β = 0.426; t = 3.529) significantly affect relationship marketing, whereas service value does not (β = 0.155; t = 1.166). Significant influence delivered by relationship marketing onto customer satisfaction with (β = 0.809; t = 20.776) while loyalty contributed (β = 0.330; t = 3.623), meanwhile satisfaction notably affects loyalty (β = 0.558; t = 6.819). Relationship marketing mediates only the effect of timeliness on customer loyalty, whereas relationship mediation was delivered by satisfaction onto marketing relation towards customer loyalty, highlighting sequential relational mechanisms in corporate logistics. These findings provide theoretical and managerial implications for improving customer retention strategies in B2B corporate logistics services.